Effect of Steam Treatment on The Shelf Life of Tomato (Solanum Lycopersicum L.) Fruits - Balogun, Olalekan Topsy; Abiola, Aborisade Titilope; Modupe, Akomolafe Olatunji (International Journal on Food, Agriculture and Natural Resources, 2024)
The effect of heating harvested fruits before storage varies depending on factors such as the fruit cultivar, heating method, and storage conditions. In this research, tomato fruits at different maturity stages were treated with steam and then stored at 28°C. Mature-green stage fruits heated at 55°C for 10 and 30 minutes showed no signs of rot for 24 days. Breaker-stage fruits heated at 55°C for 10 and 20 minutes, as well as at 60°C for 10 minutes, remained disease-free during storage. Heating at 55°C for 30 minutes enhanced the colour development of mature-green fruits, and the same effect was observed for breaker-stage fruits heated at 55°C and 60°C for 20 minutes. However, steam treatment did not effectively protect red-ripe fruits, as they decayed faster than the control group. Significant heat injury was observed only in breaker stage fruits heated for 20 and 30 minutes at 55°C, and 10 and 30 minutes at 60°C. The fungi causing decay isolated from diseased fruits were Fusarium oxysporum, Colletotrichum gloeosporioides, Rhizopus stolonifer, Geotrichum candidum, and Aspergillus niger.